LITERASI KEUANGAN SYARIAH BAGI UMKM DI MASA PANDEMI - Lavlimatria Esya Ahadi; Sri Yani Kusumasturi; Khirstina Curry; Mia Amelia; Ika Kristina (Universitas Trisakti, 2022)
The Covid-19 pandemic has had a positive and negative impact on the growth of MSMEs, based on the Katadata Insight Center (KIC), 82.9% of MSMEs felt a negative impact while the positive impact was only a small part, namely 5.9%. MSMEs of Yayasan Insan Palma Sejahtera, located in Palmerah, one of which during the pandemic also felt the impact of this pandemic, including limited capital, access to capital, lack of knowledge of financial institutions, sources of funding, lack of innovation, and borders in marketing products and decreased sales. There are many problems for MSMEs, but the most important thing is the difficulty of obtaining additional capital from financial institutions, this is due to the lack of MSME knowledge of financial institutions or funding sources, as well as the many requirements that have not been met by MSMEs. Based on the problems faced by MSMEs, for this reason, it is necessary to conduct education to increase the knowledge of MSME actors, this can be done in the form of training activities so that they can provide insight to MSME actors regarding the understanding of MSME actors towards Islamic Financial Literacy and Funding Sources for MSMEs that can be used to develop MSME businesses. The results of the training showed that MSME participants who understand and know Islamic financial institutions are 36 percent, while in utilizing their funds, only 50 percent. Based on the results of the training benefit questionnaire for MSME participants related to the level of understanding of the trainees who really understand the material provided strongly agreed by 48 percent and agreed that the remaining 26 percent did not agree.